2015
DOI: 10.1186/s13018-015-0233-5
|View full text |Cite
|
Sign up to set email alerts
|

Use of a real-size 3D-printed model as a preoperative and intraoperative tool for minimally invasive plating of comminuted midshaft clavicle fractures

Abstract: BackgroundOpen reduction and plate fixation is the standard operative treatment for displaced midshaft clavicle fracture. However, sometimes it is difficult to achieve anatomic reduction by open reduction technique in cases with comminution.MethodsWe describe a novel technique using a real-size three dimensionally (3D)-printed clavicle model as a preoperative and intraoperative tool for minimally invasive plating of displaced comminuted midshaft clavicle fractures. A computed tomography (CT) scan is taken of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 20 publications
0
46
0
6
Order By: Relevance
“…Therefore, the surgeon can accurately make surgical plans and simulate the surgical procedures before the procedure, which can highly increase the accuracy of reduction and the stability of the fixation [ 21 ]. The 3D printing also was used in ankle fractures and clavicular fractures, which showed its unique advantages, reducing the operation time, intraoperative blood loss, and the plasticity of plate [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the surgeon can accurately make surgical plans and simulate the surgical procedures before the procedure, which can highly increase the accuracy of reduction and the stability of the fixation [ 21 ]. The 3D printing also was used in ankle fractures and clavicular fractures, which showed its unique advantages, reducing the operation time, intraoperative blood loss, and the plasticity of plate [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The application of 3D printing technology in medicine provides a new way to solve the problem. However, with the wide application of the 3D printed models, [ 9 , 11 , 13 16 , 18 , 19 ] the precision and reliability of model have also been questioned. Previous studies have reported on CT image dimensional errors ranging from 0.9 to 2.16% [ 12 ] ; when images are converted to STL format, the surface of the model is converted into a large number of refined triangles that can improve the quality of image and add precision to the image-reslicing algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…In orthopedic surgery, published examples of pre-shaping titanium plates with anatomic models include use of a calcaneus model in planning for calcaneal fracture reduction (83) and clavicular models for clavicle fracture reduction (84,85).…”
Section: Anatomic Models: Pre-surgical Manipulation and Selection Of mentioning
confidence: 99%